G254(P) BP measurement in children's A&E. (27th April 2016) - Chakraborty, S; Mohan, P; Hajiyani, N; Sajjanhar, T
Abstract : Aim: Blood pressure (BP) is not measured routinely in children at triage, but should be done in a selective group of children. In our busy Children's ED we have developed a local guideline in response to critical incidents where BP was not found to have been measured. We report a retrospective audit on how successfully we followed our local policy and performed BP measurement in population of children. Methods: We performed a retrospective audit looking at the ED notes over the month of March, 2015 of all children fulfilling the criteria of our guideline who should have had a BP measurement performed at triage. We reviewed the following data: adherence to the guideline compared to the age of the child and indication for the BP measurement. A literature search was also performed to look at data from other hospitals and for any guideline available. Results: 107 records were reviewed where the patient qualified for a BP measurement according to the guideline. Only 46% had a BP measured. 5% of the children were <1 year old, 42% were 1–5 years old, (in total 47% were children under five where BP measurement can be difficult). A detailed breakdown of the patients according to the clinical indication is shown in Figure 1 . Conclusion: Blood pressure is not performed as a screening tool in the Children's ED as measuring blood pressure in children can be problematic. An appropriately sized cuff may not be available, the child could be non co-operative and the readings could be falsely high. In most EDs, clear guidance is unavailable for absolute indication of measuring BP in children. We have shown that despite the development of clear guidance on whom to measure BP we only achieve this in less than 50% of cases. This is in a busy children's ED with fully trained children's nurses. Measurement of BP is essential in a group of children either as a baseline or as a guide to their care. We therefore recommend that BP should be measured whenever possible in children's A&E particularly with the presentations mentioned in our guideline.